159k views
4 votes
(4x = y - 1
(6x - 2y = -3
substitution

2 Answers

5 votes

Answer:

x=1/2, y=3. (1/2, 3).

Explanation:

4x=y-1

6x-2y=-3

--------------

y=4x+1

6x-2(4x+1)=-3

6x-8x-2=-3

-2x-2=-3

-2x=-3+2

-2x=-1

2x=1

x=1/2

4(1/2)=y-1

4/2=y-1

2=y-1

y=1+2=3

User MattW
by
6.0k points
5 votes

Hey there! :)

Equation 1) 4x = y - 1

Equation 2) 6x - 2y = -3

We want both equations to match in a sense where both x & y are on the same side of the equal sign. To achieve this, simply subtract y from both sides in equation 1.

This will leave us with : 4x - y = -1

Now, line up the equations with one another.

1) 4x - y = -1

2) 6x - 2y = -3

Now, multiply 2 to ALL of equation 1.

2(4x - y = -1)

Simplify.

8x - 2y = -2 → We'll call this new equation 3. Now, line up equation 3 with equation 2.

6x - 2y = -38x - 2y = -2

Subtract equations from one another.

-2x = -1

Divide both sides by -2.

-2x ÷ -2 = -1 ÷ -2

Simplify.

x = 1/2

Now, plug in 1/2 for x into our first equation.

4x - y = -14(1/2) - y = -1

Simplify.

2 - y = -1

Subtract 2 from both sides.

-y = -1 - 2

Simplify.

-y = -3

Divide both sides by -1.

y = 3

So, our answer is : x = 1/2, y = 3 OR (1/2, 3)

~Hope I helped!~

User Caughtinflux
by
6.1k points